Prospective Randomized Controlled Clinical Trial of the Long-Term Effects of Omeprazole on Healthy Dogs - Laura Gil-Vicente; Germán Martín; Carme Soler; Anna Vila; María Rocío Saiz; Paula F. Navarro (Animals, 2024)
The use of omeprazole as a preventive treatment for gastrointestinal ulcers in veterinary medicine has been questioned during previous years. The aim of the present study is to assess the long-term effect of omeprazole on cobalamin and serum gastrin levels in healthy dogs. Eighteen healthy dogs were included: 10 in the control group and 8 in the omeprazole group. Three samples were collected: before starting the treatment (T0), 30 days after the start of treatment (T1), and at 60 days (T2). The mean cobalamin value (ng/L) in the control group was 481.4 (±293.70) at T0, 481.4 (±170.21) at T1, and 513.2 (±174.50) at T2. In the omeprazole group, the values were 424.62 (±161.57) at T0, 454.5 (±160.96) at T1, and 414.87 (±127.90) at T2. No statistically significant changes were detected in cobalamin levels between the three-time period in both study groups. These results agree with previous findings in felines but contrast with human medicine studies. The median gastrin values (pg/mL) in the control group were 62.45 [30.17–218.75] at T0, 76.06 [30.67–199.87] at T1, and 63.02 [35.81–176.06] at T2. The median gastrin value in the omeprazole group was 67.59 [55.96–101.60] at T0, 191.77 [75.31–1901.77] at T1, and 128.16 [43.62–1066.46] at T2. Statistically significant differences were detected (p = 0.008), indicating an increase in gastrin levels after initiating treatment with omeprazole. In conclusion, the increased levels of gastrin observed in this population underscore the importance of conducting a comprehensive clinical assessment to identify potential gastrointestinal disorders, particularly in consideration of the usage of omeprazole as a preventive treatment.